Sustainable Plant-Assisted Production of Silver Nanoparticle Hybrids for Antimicrobial Use: Insights from Chromolaena odorata and Patchouli Oil - Pebriani, Liska Nova; Kemala, Pati; Idroes, Ghazi Mauer; Fatriasari, Widya; Khairan, Khairan; Idroes, Rinaldi (Grimsa Journal of Science Engineering and Technology, 2026)
This study developed a green synthesis approach for silver nanoparticles (AgNPs) using ethanolic extracts of Chromolaena odorata leaves (LCo) collected from geothermal areas, followed by post-synthesis incorporation of patchouli oil (PO) to improve antimicrobial performance. The synthesis was optimized using Response Surface Methodology (RSM) based on AgNO₃ concentration and pH, with surface plasmon resonance (SPR) as the response indicator. Successful formation of AgNPs was confirmed by characteristic SPR absorption in the visible region. Structural and morphological analyses indicated the involvement of plant-derived functional groups in nanoparticle stabilization, with predominantly spherical particles and some aggregation observed. Antimicrobial testing against Staphylococcus aureus, Escherichia coli, and Candida albicans showed that the PO-AgNPs-LCo system exhibited a slightly higher inhibition zone compared to AgNPs-LCo alone, indicating a marginal enhancement in antimicrobial activity. These results suggest that geothermal-derived plant extracts can be effectively utilized for AgNPs synthesis, while post-synthesis incorporation of natural oils may provide additional functional modification. However, the observed enhancement remains limited, indicating the need for further optimization and mechanistic studies. Overall, this work highlights a simple and eco-friendly route for developing plant-based antimicrobial nanomaterials.